Potential marketability of graduates from bachelor of production operations management (Hons),Universiti Utara Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)

(untitled)
The Second Malaysian Industrial Master Plan (IMP): (1995-2005) had identified the manufacturing sector as a contributor to Malaysia’s economic development. Therefore, to materialize the objective of IMP2, Malaysia needs to depend on the effectiveness and efficiency of its technocrats and operations managers.